The Influence of Acupressure Therapy with Complementary Techniques on LI-4 Point in Alleviating Dysmenorrhea in Adolescent Girls at SMPN 3 Godean, Yogyakarta - Safety, Henny; Suryaningsih, Endang Koni (Menara Journal of Health Science, 2024)
Dysmenorrhea or menstrual pain is one of the most common gynecological complaints in female adolescents, so many experience dysmenorrhea which interferes with their daily activities; hence, it is common for them to be absent from school. Acupressure is a traditional medicine originating in China. It is a treatment given by pressing on a certain point gently using the index finger or thumb. Pressing stimulates the flow of energy at the meridian point. The present study aimed to determine the effect of acupressure therapy on reducing menstrual pain (dysmenorrhea) in students of SMPN (Public Junior High School) 3 Godena. The study used a quasi-experimental method with a nonequivalent control group design. The population of the study was 110 female students with 30 respondents as samples from grade VII chosen with a purposive sampling technique. The instrument used was NRS (Numeric Rating Scale). The analysis used in the research was univariate and bivariate analysis (Wilcoxon). The results showed that there was a significant difference between the control and experimental groups (0.001). Giving acupressure at LI-4 point with a duration of 3-5 minutes can reduce menstrual pain in adolescents at the research site. It is hoped that the study can be a reference to complete related information in the future, especially acupressure therapy in treating dysmenorrhea.